Efektivitas Penggunaan Media Alat Permainan Edukatif (APE) Berupa Boneka Jari Hewan Dalam Meningkatkan Kemampuan Berbahasa Anak Usia Dini - Nadia Putri Utami; Fatrica Syafri Syafri (UIN Fatmawati Sukarno Bengkulu, 2026)
This study aims to determine the effectiveness of using educational play media (APE) in the form of animal finger puppets to improve the language skills of early childhood learners at PAUD IT Al-Qiswah, Bengkulu City. The background of this research is based on findings that some children in Group B still experience delays in language development, particularly in expressive language skills such as speaking, expressing opinions, and retelling stories. This study employed a quantitative approach using a Pre-Experimental One Group Pretest-Posttest Design. The research sample consisted of 22 children aged 5–6 years in Group B. The instruments used were teacher activity observation sheets and child language skill assessment sheets based on the indicators of Permendikbud No. 146 of 2014. Data were analyzed using normality tests, homogeneity tests, and t-tests to determine the significant differences between pretest and posttest scores. The results showed an improvement in children’s language abilities after receiving treatment using APE finger puppets. Children became more capable of repeating simple sentences, answering questions, understanding storylines, and retelling stories in a more coherent manner. Thus, finger puppet media proved to be effective as a learning tool that enhances early childhood language skills in an enjoyable and meaningful way.